Ver no mundo dos cegos e ser cego no mundo dos que vêem - SILVA, Italo Rafael Tavares da (2020)
This research was part of the experiences lived in a thematic axis of undergraduate course in sciences, mathematics and languages, with emphasis on the theme of inclusion. The main objectives are: to reflect on the difficulties of the low vision alliances and to identify the pedagogical aspects in the classroom that are in agreement with the information about the visual literature. The research is a case study and the analysis is done through narrative. The data collection was done through systematic, conversation with a student and accompaniment in the classroom. The results indicate that teacher training occupies a prominent place on the subject, where it is necessary to have basic theoretical-practical knowledge of issues such as attention to diversity and inclusion, use of methodologies that favor the development of people with low vision and who, minimally, the special needs within a classroom. We therefore consider that teaching work must be fundamentally collaborative so that the peculiar barriers of its will are overcome. Finally, work may be important in relation to elementary education where it receives more than one education without differences to differences.